Penerapan Akad Mudharabah dan Musyarakah dalam Sistem Ekonomi Syariah - Irfan Abdul Fattah; Madian Muhammad Muchlis (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
Islamic economics is an economic system based on the principles of Islam, primarily derived from the Qur'an and Hadith, emphasizing justice, balance, and the prohibition of unethical practices such as usury (riba) and gharar. This system provides a more ethical and equitable alternative to the conventional interest-based economic system. As awareness of social justice and sustainability grows, Islamic economics has expanded, not only in Muslim-majority countries but also across various parts of the world. This journal aims to provide a comprehensive overview of the fundamental concepts of Islamic economics, its implementation across various sectors such as banking, trade, and industry, and the challenges faced in its development and implementation. Additionally, this study highlights how Islamic principles can be applied to promote more inclusive and sustainable economic development, as well as the role of Islamic financial institutions in the global economy. This research is expected to provide insights for practitioners, academics, and policymakers in advancing the broader and more competitive development of Islamic economics.